ANALISIS KEKUATAN PAVING BLOCK MENGGUNAKAN ABU SEKAM PADI DAN LIMBAH PLASTIK - Desi Putri; Reksa Dimas Safitroh (Jurnal Sipil Krisna, 2022)
Paving blocks are often used for pavements, yards, and parks. The research uses ricehusk ash as a substitute for cement and plastic waste as a substitute for sand in order toovercome the waste of rice husk ash and plastic waste that has accumulated and has not beenwidely utilized, as well as empowering communities around the waste to be able to takeadvantage of the waste. The purpose of this study was to analyze the compressive strength ofpaving blocks when the cement and sand were substituted with rice husk ash and plastic waste.The study was conducted experimentally with two stages of testing. At the initial stage of theresearch preliminary testing is carried out which includes testing the physical properties of thematerial. The second stage of making test objects using plastic waste 0%, 5%, 10%, 15%, 20%by weight of sand, and 10% of rice husk ash by weight of cement. Tests were carried out at 7days, 14 days, and 28 days. Based on the results of the compressive strength test at 28 days ofage, the compressive strength of paving blocks was 20,083 MPa, 26,413 MPa, 30.666 MPa,22.166 MPa, 16.083 MPa. From the test results obtained the value of the optimum compressivestrength is in the variation of 10% plastic waste and 10% rice husk ash. By SNI 03-0691-1996the compressive strength value is included in the B quality used for parking lots and becomesan alternative environmentally friendly construction material.